Development of Android-based digital teaching materials on Push Technique Material in Table Tennis Games - Kadek , Dimas Dwipayana; I Putu, Panca Adi; Ni Putu , Dwi Sucita (Jurnal Pendidikan Kepelatihan Olahraga Undiksha, 2024)
In university courses, particularly table tennis classes, this digital teaching material is essential to support the optimal execution of the learning process. This study aims to develop Android-based digital teaching materials focused on the push technique in table tennis. The research adopts a development study approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The developed product underwent validation by experts in content, instructional design, educational media, and field practice. The product testing included individual trials with three students, small group trials with six students, and large group trials with twenty-four students. Data were collected using questionnaires and analyzed using descriptive quantitative analysis. The results of the study showed that the content expert validation yielded a score of 98%, categorized as good, the instructional design expert validation scored 96%, categorized as very good, the educational media expert validation scored 90%, categorized as very good, the field practitioner expert validation scored 93%, categorized as very good, the individual trials scored 96%, categorized as good, the small group trials scored 98%, categorized as good, and the large group trials scored 92%, categorized as very good. Therefore, the developed product, an Android-based digital teaching material on the push technique in table tennis, serves as a learning resource that can enhance the quality of learning during the instructional process.